Realistic Soft-Core Potentials in the Bound Three-Nucleon System - Dijk, Wytse van (My University, 1968)
Variational calculations of the bound three-nucleon system have been done. Gaussian type trials functions were chosen which led to an explicit decomposition of the three-body wave function into components which display definite two-body LSJ dependence. The calculations were done with three soft-core potentials and purely attractive potential. It was found that regardless of the number of terms the superposition of Guassians was inferior to exponential trial functions. A correction in the binding for the Gaussian type function was applied and it was not inconsistent with the experimentally observed binding of the triton. The Coester-Yen potential, although it is "unrealistic", gives binding energy and radius of the triton which are in close agreement with experiment.
Title: Realistic Soft-Core Potentials in the Bound Three-Nucleon System, Author: Wytse V. Dijk, Location: Thode